The Effect of Action Observation Training on Balance and Sit to Walk in Chronic Stroke: A Crossover Randomized Controlled Trial. Issue 4 (4th July 2018) - Kim, Jin-Cheol; Lee, Hyun-Min
ABSTRACT: The aim of this study was to investigate the effects of an action observation training on balance and sit to walk in chronic stroke. Twenty-four chronic stroke patients participated in this study. Participants were randomly allocated to either the landscape imagery observation physical training group (LIOPT) or the action observation physical training group (AOPT). LIOPT observed a landscape picture for 2 min 30 s while the AOPT group observed related video recording. Both groups underwent a physical training session after the observation session for 12 min 30 s and the sessions were repeated twice a day, 3 times a week for 6 weeks. Outcome measures included Time Up and Go Test (TUG), Dynamic Gait Index (DGI), Weight Distribution Index (WDI), and limit of stability (LOS). Between-group and within-group comparisons were analyzed using the Mann-Whitney U test and Wilcoxon signed rank test, respectively. The AOPT and LIOPT groups have shown statistically significant differences in TUG, DGI, WDI, and LOS over time. However, no significant difference was observed in terms of TUG, DGI and WDI, but only in LOS between groups. These findings suggest that action observation training and physical training are effective to improve sit to walk and balance ability of chronic stroke patients.